Kepemimpinan Guru dalam Membangun Budaya Disiplin di MA Hidayatul Islamiyah - Nanda Nur Zakiya; Nadya Arrifni Ilma; Syihada Hilwati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Character Education, especially in terms of discipline, is a major concern in the learning process that occurs in schools. The role of teachers is not only limited to teaching, but also includes being role models, motivators, and mentors who can build a disciplined atmosphere among students. This study adopted a qualitative approach with data collection methods including observation, interviews, and documentation. The research findings indicate that the culture of discipline in madrasas is greatly influenced by the implementation of strict rules, the provision of rewards and punishments, and the persuasive approach and role models from teachers. In addition, there are supporting factors such as the existence of madrasa regulations and good examples from teachers, as well as inhibiting factors such as environmental influences and the use of gadgets. In conclusion, the development of a culture of discipline in madrasas requires cooperation between teachers, students, and the environment, as well as the right strategy to create a conducive and disciplined learning atmosphere.